Evaluation of the technical and environmental feasibility of replacing a steam generation unit with wind turbines at the Zawia refinery, Libya (Al-Farooq Journal of Sciences, 2026)
This study provides a comprehensive technical and environmental assessment of the traditional steam power generation unit (3.5 MW) that operates on heavy fuel oil at the Zawia Refinery, Libya, and examines the replacement of it with a wind farm based on ENERCON E-53 (800KW) wind turbines. Wind speed data from the reference height (50 m) to the height (80 m) were analysed using the power law method, and with the Weibull distribution, the expected power and annual energy production for the Enercon E-53 wind turbine were estimated using the turbine's power curve, in order to determine the number of wind turbines required as an alternative to the steam turbine. The environmental impact of the annual CO2 emissions from the steam turbine and wind turbines was also calculated. Based on the results obtained, it was found that energy production increases with the height of the turbine axis. A wind farm consisting of 12 turbines was proposed, producing approximately 26 GWh/year, which is equivalent to the annual production of the steam power generation unit. Environmental assessments based on life cycle emission factors indicated that replacing the steam unit with the proposed wind farm could reduce carbon dioxide emissions from approximately 20,848 tonnes of CO2 annually to nearly 391 tonnes of CO2 annually, equivalent to a reduction of over 98%. Based on the results, it has been shown that integrating wind energy into industrial facilities is a technically feasible and environmentally sustainable solution to reduce reliance on fossil fuels and support the transition to clean energy systems in Libya.
Keywords: wind energy, Weibull distribution, wind turbine (Enercon E-53), Zawiya refinery, carbon emissions